CONGREGATION AND POLITICS: POLITICAL BEHAVIOURS OF SOCIAL RELATIONS COMMUNITY MEMBERS - Dogan, Adem (Selcuk Univ, Inst Turkish Studies, 2015)
There are various factors on policial behaviour. It's a fact that social relation groups render are important between these factors. The recent political choices of communions as a social relations group in our country, and the effects of their members on political behaviour is in discussed in other sizes. There is a presupposition that members of communions operate with a sense of common will, within a mutual interest phrame in a social relations web. In this sense, although various evaluations have been carried out related with the political behaviours of communion members, no academic study is available in the literature. Political developments in our country have turned the effect of the communion members on the vote rate of communions into an important matter of debate. It was attempted to measure the memberships to communions, reasons for joining a communion, and the political behaviours of communion members all over Turkey in this study. A poll was conducted on 2600 voters living in 12 different cities. 2579 surveys were evaluated as a resolt of this research, because there were inaccurate polls. In accordance with the results, it can be mentioned that there's a communion fact in Turkey, however, in accordance with the results of the latest analysis it's recorded that the rate of the ones who revealed that they were members of a communion is 3.9%, which is a quite low rate. Nevertheless, the prominent persons of communions are conducting the political behaviours of communion members, and in this sense it's found out that some communion members vote the party or the candidate who is recommended by the leaders of their communion.
Keywords: poitical behaviours; social relations; communions; political